Speed Control of a Single-Phase Induction Motor Using a Fuzzy Logic Based Hysteresis Band PWM - Yılmaz, Ece; Ünal, Sencer; Özdemir, Mehmet (Hibetullah KILIÇ, 2024)
Single-phase asynchronous motors are preferred in the industry due to their significant features such as robust construction, easy maintenance, and ability to operate in different ambient conditions. They are widely used in various types of automated control systems, cooling and ventilation appliances, and household appliances. Although the structure of the single-phase induction motors is quite simple, modeling and speed control of them are very difficult due to their nonlinear structure. Since traditional speed control methods are not sufficient in nowadays, various methods are being investigated for the speed control of these motors. One of them is to control the speed of a single-phase induction motor by changing the voltage waveform via the power electronic components. In addition to this method, fuzzy logic controller can be preferred in the systems that are difficult to analyze and it does not require a mathematical model. For this reason, in this study, a PWM controlled AC chopper circuit and fuzzy logic controller, which is one of the faster and cheaper methods, are proposed for the speed control of a single phase induction motor. Thus, better results are obtained from the fuzzy logic controller. The system is modeled by MATLAB/Simulink simulations and the results are validated.
Keywords: Electrical Machines and Drives; Elektrik Makineleri ve Sürücüler